Lattice models of statistical mechanics and their applications - Ganikhodjaev, Nasir (2011)
Lattice models are caricatures invented to illuminate various aspects of elementary statistical mechanics, especially the phenomena of phase transitions and spon- taneously broken symmetry. This paper is an attempt to present the basic ideas of the subject and its application to a wider audience.